Detection of Muscle Injury in A Case Evaluated for Judicial Report - Güler, Hülya; Kaya, Ahsen; Meral, Orhan; Argın, Mehmet (The Bulletin of Legal Medicine, 2016)
Cases where stab wounds are sutured with no detailed description of the wound features are common in practice and therefore problems regarding judicial reports arise in such cases. In this case report, it was aimed to point out the importance of Magnetic Resonance Imaging (MRI) in terms of medicolegal evaluation due to its employment in a case evaluated for judicial report where wound characteristics were poorly described at an outside center and muscle injury findings were noted on MRI. Male patient aged 21 was sent for evaluation approximately 2.5 months after injury, due to lack of information on muscle injury, conclusion on whether the injury was “treatable with simple medical intervention or not” could not be reached. An MRI scan following Orthopedics & Traumatology consultation revealed muscle injury and the judicial report was prepared accordingly. Although MRI is a useful tool in detection of the wound characteristics, when its cost is considered, it becomes evident that detailed and accurate description of the wound features by the first physician examining the case is crucial for judicial report process.